Metabolic Architecture of the Cereal Grain and Its Relevance to Maximize Carbon Use Efficiency . Issue 3 (22nd September 2015) - Rolletschek, Hardy; Grafahrend-Belau, Eva; Munz, Eberhard; Radchuk, Volodymyr; Kartäusch, Ralf; Tschiersch, Henning; Melkus, Gerd; Schreiber, Falk; Jakob, Peter M.; Borisjuk, Ljudmilla
Abstract : Noninvasive technologies and modeling demonstrate how the metabolism of different grain organs adjusts to fluctuating environments. Abstract: Here, we have characterized the spatial heterogeneity of the cereal grain's metabolism and demonstrated how, by integrating a distinct set of metabolic strategies, the grain has evolved to become an almost perfect entity for carbon storage. In vivo imaging revealed light-induced cycles in assimilate supply toward the ear/grain of barley ( Hordeum vulgare ) and wheat ( Triticum aestivum ). In silico modeling predicted that, in the two grain storage organs (the endosperm and embryo), the light-induced shift in solute influx does cause adjustment in metabolic flux without changes in pathway utilization patterns. The enveloping, leaf-like pericarp, in contrast, shows major shifts in flux distribution (starch metabolism, photosynthesis, remobilization, and tricarboxylic acid cycle activity) allow to refix 79% of the CO2 released by the endosperm and embryo, allowing the grain to achieve an extraordinary high carbon conversion efficiency of 95%. Shading experiments demonstrated that ears are autonomously able to raise the influx of solutes in response to light, but with little effect on the steady-state levels of metabolites or transcripts or on the pattern of sugar distribution within the grain. The finding suggests the presence of a mechanism(s) able to ensure metabolic homeostasis in the face of short-term environmental fluctuation. The proposed multicomponent modeling approach is informative for predicting the metabolic effects of either an altered level of incident light or a momentary change in the supply of sucrose. It is therefore of potential value for assessing the impact of either breeding and/or biotechnological interventions aimed at increasing grain yield.